(3JaSjQ GdaGJMIs
(3ChdgG (B:s
(3GdMeO GdhUa HGdLejd Ydi LgI GdJaVjd hgh QLY HGdEHJOGA hCUdg GdfUH s
(3BNQgG (B:s
(3hbGd Efg cGdNJe Ydi GdcJGH hdjS ef GdbQBf HOdjd Cfg de jKHJ ai GdeUGMa GfJgi PcQ ef GdfSai GfJgi hcai hSdGe Ydi YHGOg GdPjf EUWai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRGfI GdYGeI HGdQHGW (B_ (3GdeZQH (B(364d) s
Keywords: (3GdeLGejYs